Measuring progress against cancer in the Azores, Portugal: Incidence, survival, and mortality trends and projections to 2025. (December 2020) - Forjaz, Gonçalo; Chen, Huann-Sheng; Howlader, Nadia; Rego, Raul; Rodrigues, Vitor; Mariotto, Angela B.
Highlights: This is the first study in which incidence, survival, and mortality are interpreted concomitantly to evaluate progress against cancer in a specific region of Portugal, the Azores archipelago. Much of the progress has been driven by treatment advances, as seen by survival improvements and decreases in mortality. Incidence and mortality increased for colorectal cancer in men and lung cancer in women. Reducing tobacco use and obesity are cancer control priorities within the region. Abstract: Background: Measuring progress against cancer is more accurate when trends in incidence, survival, and mortality are interpreted simultaneously. Our study aims to analyze how these key metrics have evolved over time in the Azores, Portugal. Methods: Data for incident cases diagnosed in 1997–2016 and followed up through December 31, 2017 were obtained from the Azores Cancer Registry. Data for cancer deaths that occurred in 1991–2016 were obtained from Statistics Portugal. To estimate temporal trends, we applied a joinpoint model to age-adjusted rates. We estimated five-year net survival within the framework of relative survival using the Pohar-Perme estimator and predicted the number of cases and deaths in 2025. Results: In men, incidence and mortality decreased for stomach, larynx, and prostate cancer. In women, mortality decreased for breast and cervical cancer. Five-year relative survival improved for several cancers, with the most pronounced improvements for prostate cancer in men and colorectal cancer in women (24.1 and 27.9 percentage point absolute increase, respectively). Conversely, incidence and mortality increased for colorectal cancer in men and lung cancer in women. The incidence and mortality burdens are both expected to increase in 2025. Conclusion: Overall, progress against cancer in the Azores has been mixed, and much of the progress has been driven by advances in treatment. Statistics for lung cancer in women and colorectal cancer in men are a call to action for policymakers. Reducing tobacco use and tackling the obesity epidemic are the two public health priorities for cancer control within the region.